Net clinical benefit of antithrombotic therapy for atrial fibrillation patients with stable coronary artery disease - Lee, So-Ryoung; Jung, Jin-Hyung; Choi, Eue-Keun; Lee, Seung-Woo; Kwon, Soonil; Park, Ji-Suck; Kang, Jeehoon; Han, Kyung-Do; Park, Kyung Woo; Oh, Seil; Lip, Gregory Y. H. (Frontiers in Cardiovascular Medicine, 2022)
Objectives To compare the net clinical benefit of oral anticoagulant (OAC) monotherapy to OAC plus single antiplatelet therapy (SAPT) in patients with atrial fibrillation (AF) and stable coronary artery disease (CAD) at 1- and 3-year after percutaneous coronary intervention (PCI). Background It has not been studied whether the net clinical benefit of the antithrombotic treatment options differs depending on the elapsed time from the index PCI. Methods Using the Korean nationwide claims database, we included AF patients who underwent PCI from 2009 to 2019 and constructed two cohorts: 1- and 3-year after PCI. In each cohort, the baseline characteristics of two groups were balanced using propensity score weighting. Ischemic stroke, myocardial infarction, major bleeding, and composite clinical outcomes were analyzed. Results Among patients with 1-year after PCI, OAC monotherapy (n = 678), and OAC plus SAPT (n = 3,159) showed comparable results for all clinical outcomes. In patients with 3-year after PCI, OAC monotherapy (n = 1,038) and OAC plus SAPT (n = 2,128) showed comparable results for ischemic stroke and myocardial infarction, but OAC monotherapy was associated with a lower risk of composite clinical outcomes (HR 0.762, 95% CI 0.607–0.950), mainly driven by the reduction of major bleeding risk (HR 0.498, 95% CI 0.345–0.701). Conclusion Oral anticoagulant monotherapy may be a comparable choice for patients with AF and stable CAD compared to OAC plus SAPT. In patients with stable CAD more than 3-year after index PCI, OAC monotherapy would be a better choice, being associated with less major bleeding and a positive net clinical benefit.